Reproduction and Growth Performance of Kampung Unggul Balitbangtan (KUB) Chicken Cross - Galuh Adi Insani; Dyah Maharani; Stefanie Silvia; Vellina Putri Handayani; Wihandoyo Wihandoyo (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
In Indonesia, one of the sources of regional livestock genetic diversity is the kampung chicken. This study aimed to assess the development and reproductive potential of F1 Kampung Unggul Balitbangtan (KUB) crosses (KUB roosters with different types of combs crossed to layer chickens). This research was conducted at a private chicken company in Gunungkidul regency using 40 KUB roosters and 320 layer chicks. The KUB roosters were separated into four groups based on their comb types: single, walnut, and double. Each set of ten males was housed in a single cage, with a male-to-female ratio of one to eight (male and female). Observed reproductive variables included egg weight (EW), hatch weight (HW), fertility, hatchability, number of eggs, number of day-old chicks (DOCs), and number of saleable chicks. The body weight (BW) of the offspring at ages ranging from DOC, 4, 8, to 12 weeks of age is one measure of their growth characteristics. The analysis of variance using a one-way design and the DMRT test were performed to describe the difference in growth and reproductive performance across groups. As a result, each comb type revealed a significant difference in EW, HW, fertility, hatchability, egg and chick production, DOC, and saleable chick production (P<0.05). Compared to other combs, the single comb performed the best in terms of EW, HW, fertility, number of eggs, and number of DOC. The most hatchable and sellable chicks were from walnut comb. Therefore, comb size has a positive correlation with chicken reproduction and productivity. Comb type groups have no effect on BW at 12 weeks (P>0.05), while they significantly affect BW for DOC at 4 and 8 weeks (P<0.05). The rose comb shows BW at its maximum point. In conclusion, the rose comb has the biggest body weight and the single comb has the best reproductive performance in comparison to other comb types.